SISTEM PERINGATAN DINI DAN PENENTU TINGKAT BAHAYA KEBAKARAN MENGGUNAKAN MIKROKONTROLLER ATMEGA 16 - Paronda, A. Hafid; Marini, Sri; Hidayat, Nurul (Program Studi Teknik Elektro Fakultas Teknik Universitas Islam 45 Bekasi, 2013)
This thesis describes the design of an early warning system against fire, the overall system consists of hardware and software. The hardware system consists of temperature sensors and gas sensors that detect signs of fire the detection of gas, smoke and increase in temperature in a room. All detected information is processed by a microcontroller atmega16 that function ring alarm form buzzer, exos fan and hydrant based on predefined parameters, namely ? 36 ° for safe levels indicated green, ?46° for standby levels indicated yellow, ?60° for alert levels indicated red and last ?80° for evacuation levels indicated red and to transmit the data to the server computer via serial communication lines. Borland Delphi7 as software (user interface) on a computer server function display and record the results of the two sensor readings along with the details of time, date, month and year.